BIOINDEKS ZOOPLANKTON DI PERAIRAN PULAU BUNAKEN - Kezia Keren Erika Tampi; Joice R.T.S.L Rimper; Veibe Warouw (JURNAL PESISIR DAN LAUT TROPIS, 2021)
The city of Manado has several islands which are strategic places with the development of marine potential. One that is so potential is the waters of Bunaken Island and the forms of activity in Bunaken Island waters vary widely. The purpose of this study is to determine the abundance value and biological index and to analyze the condition of the waters in the waters and to see the comparison at each research station. The results of zooplankton identification consisted of 7 genera including all research stations. The results of the analysis of the highest abundance data were at the third station (8.4822 ind / l) and the lowest abundance value was at the first station (7.4220 ind / l). The results of the biological index analysis obtained are as follows: the average diversity value at three stations is 1.08, the uniformity is 0.98 and the dominance is 0.20. The results of the Morisita index for each station are: stations. Which means the value of the distribution pattern is three groups, and the others are uniform in each research genus, the overall distribution is uniform.Keywords:Â  Zooplankton, Bunaken Island waters, Abundance, Bioindex